PENGARUH STRUKTUR DAN TEKTONIK DALAM PREDIKSI POTENSI COALBED METHANE SEAM PANGADANG-A, DI LAPANGAN “DIPA”, CEKUNGAN SUMATERA SELATAN, KABUPATEN MUSI BANYUASIN, PROVINSI SUMATERA SELATAN - Ragil Pratiwi; Hadi Nugroho; Dian Agus Widiarso; Rana Lesmana (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
The increasing of oil and gas and energy crisis nowadays has been causing the explorationist look forthe new energy sources such as gas in shale and coal which more environmentally friendly. SouthSumatera Basin is one of Indonesian Basin which has a large potency with 183 tcf. Methane gas isstored in natural fracture of coalbeds called cleat. Cleat was produced during coalification andtectonism process.The aim of this study is to evaluate the influence of structures and tectonism processes towards theCBM potency in an area. The research methods were done by desciptive and analysis methods.Descriptive method was done by describing secondary data which contain rock mass data, andanalyzing method was done by analyzing subsurface data consist of seismic and wireline log. Thosedata were used to determine the sweetspot area and calculate gas in place in target zone of CBM.Based on geologic structure analysis, primary orientation trends which configure geologic structuresis northeast-southwest, it is a Compression Phase of Miocene-Recent. This stress configured sincline,sinistral strike-slip fault, and normal faults in tensional phase. The interesting area of CBMexploration or sweetspot area located in the northeast area, with normal faults which control fracturepermeability reach 12,22 mD, high thickness reach 14 – 18 feet (4,7 – 6 meter), and CBM targetdepth of < 6000 feet (2000 meter), and gas in place calculation reach 0,742 tcf. Completiontechniques for CBM target in study area with relatively low permability are hydraulic fracturingcompletion and horizontal well with direction of well is relatively northeast-southwest whichperpendicular with face cleat.